SOCIO-PEDAGOGICAL COMPETENCES OF SPECIALISTS IN SOCIAL WORK WITH CHILDREN AND YOUTH WITH DISABILITIES AND WITH THEIR FAMILIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article raised the question of specialization in: social work with persons who have disabilities. Criteria of social and pedagogical competences, competent approach and actual needs of practicing specialists, their preparation for work with persons who have disabilities are considered.
Keywords: social-pedagogical competences of specialists of social work, competence, social work, professional portrait of specialist of social work with persons with disabilities.